INOVASI TEKNIK PENGUMPULAN SPAT KERANG HIJAU YANG EFEKTIF UNTUK PEROLEHAN BENIH BERKUALITAS DI PERAIRAN DESA NGGOJOYO, KECAMATAN WEDUNG KABUPATEN DEMAK - Restiana Wisnu Ariyati; Sri Rejeki; Lestari Lakshmi Widowati (Universitas Mataram, 2022)
Nggojoyo coastal village, Wedung sub-district, Demak district is a mangrove greenbelt area that needs to be protected from damage and illegal logging. The waterfront mangrove greenbelt are fertile waters. The collection of green mussel spat is an alternative activity that is introduced to the community of Nggojoyo village as a livelihood, by installing bamboo and rope constructions in the water front mangrove greenbelt for the spat attachment. The purpose of this community service is to introduce appropriate technology to collect green mussel spat in the waterfront mangrove greenbelt as well as to protect the mangrove greenbelt from damage. The method used in this community service is counselling on how to collect green mussel spat and practicing of making and bamboo and rope constructions as a place for spat attachment. Monitoring is carried out monthly during the service that was carried out from early February to the end of May 2022. The results of community service show that bamboo construction as a green mussel spat collector which was installed for 2 months was heavily attached by green mussel spat at the size between 0.5 - 1 cm. Therefore, it can be concluded that the collection of green mussel spats can be done in waterfront mangrove greenbelt of Nggojoyo village.